Apakah Perusahaan dengan ESG Tinggi Memiliki Kinerja Keuangan yang Lebih Baik? - Renfiana, Lilis; Hendri, Loni; Idaman, Northa (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
Environmental, Social, and Governance (ESG) issues have gained global prominence in sustainable investing, yet empirical evidence on their relationship with corporate profitability in emerging markets like Indonesia remains limited and inconsistent. This study examines differences in profitability, measured by Return on Assets (ROA), among companies with varying ESG performance categories on the Indonesia Stock Exchange. A comparative quantitative method was applied to a sample of 84 companies classified into three ESG categories (Good, Medium, Poor) based on Sustainalytics scores. Data analysis employed descriptive statistics, Shapiro-Wilk normality test, and the non-parametric Kruskal-Wallis test. The results revealed no statistically significant differences in ROA among the three ESG groups (H = 4.452, p = 0.108). An interesting finding emerged from the numerical pattern showing the